Penguin Gandhi reader - Rudrangshu Mukherjee; MUKHERJEE (Rudrangshu) (New Delhi Penguin Books, 1993)
Mohandas Karamchand Gandhi (1869-1948) was born in Porbander on the western coast of India. His childhood and early upbringing were undistinguished but as an adult he initiated and was involved in a series of novel forms of peaceful protests which established him as one of the most important leaders of the twentieth century and one whose message and relevance transcended national boundaries. This meticulously edited volume culled from the Collected Works of Gandhi contains a representative selection of his writings focusing on themes which were central to Gandhi's philosophy.
Keywords: Biography; Mahatma Gandhi